COMPOSIÇÃO DE WEB SERVICES SEMÂNTICOS NO AMBIENTE ICS DE COMÉRCIO ELETRÔNICO - Almeida, Carlos Roberto Baluz (2004)
The ICS (Intelligent Commerce System), a developing project of the Intelligent Systems Lab (LSI) at Federal University of Maranhão (UFMA), under Prof. Dr. Sofiane Labidi´s supervision, is a project that has the objective of develop an Electronic Commerce System, in the B2B (Business to Business) category, effectively intelligent. It is based in the technology of intelligent mobile agents and has five phases in its life cycle: User Modeling, Matchmaking, Negotiation, Contract Formation and Contract Fulfillment. The Matchmaking is the process in which agents that represent traders (buyers and sellers), that are interested in the exchange of economic values, are put in touch with their potential business counterparts. The enrichment of the matchmaking process is the main focus of this work. Nowadays in the ICS, the matchmaking process only matches simple services. Our contribution is to enrich the actual matchmaking process allowing the composition of services, that is, simple services can add its capacities and form complex services with the goal to return a greater number of positive responses. To do this, we use ontologies allied to AI planning techniques to provide the discovery of complementary services and the posterior composition of them to elaborate more complex services.